2010
DOI: 10.1007/s11627-010-9283-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of xylanase in transgenic tobacco for industrial use in bioenergy and biofuel applications

Abstract: Xylanases are used in various agricultural and industrial applications. A synthetic, modified, codonoptimized xylanase gene (XynZ) from Clostridium thermocellum was expressed in transgenic tobacco plants. The coding sequence of XynZ was placed between the modified Mirabilis mosaic virus full-length transcript promoter with duplicated enhancer domains and the terminator sequence from the rbcSE9 gene. Three constructs were developed to evaluate XynZ expression levels by targeting gene products into the cytosol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
(33 reference statements)
0
24
0
1
Order By: Relevance
“…X 1 xylose, X 2 xylobiose, X 3 xylotriose, X 4 xylotetraose, MeGX 1 methylglucuronoxylose, MeGX 2 methylglucuronoxylobiose, MeGX 3 methylglucuronoxylotriose, MeGX 4 methylglucuronoxylotetraose transformation approach (Laliberté et al 1992). Maximum xylanase expression levels of 3-5% of the total soluble protein in mature leaves were reported following gene transfer to the nucleus (Herbers et al 1995;Bae et al 2006;Yang et al 2007;Chatterjee et al 2010). However, an excessive line to line variation exists in nuclear transformed plants due to copy number, position effects and gene silencing mechanisms (Eike et al 2005;Vaucheret 2006;Fischer et al 2008), therefore requiring the screening of a large number of transgenic plants to identify those with highest expression.…”
Section: Discussionmentioning
confidence: 99%
“…X 1 xylose, X 2 xylobiose, X 3 xylotriose, X 4 xylotetraose, MeGX 1 methylglucuronoxylose, MeGX 2 methylglucuronoxylobiose, MeGX 3 methylglucuronoxylotriose, MeGX 4 methylglucuronoxylotetraose transformation approach (Laliberté et al 1992). Maximum xylanase expression levels of 3-5% of the total soluble protein in mature leaves were reported following gene transfer to the nucleus (Herbers et al 1995;Bae et al 2006;Yang et al 2007;Chatterjee et al 2010). However, an excessive line to line variation exists in nuclear transformed plants due to copy number, position effects and gene silencing mechanisms (Eike et al 2005;Vaucheret 2006;Fischer et al 2008), therefore requiring the screening of a large number of transgenic plants to identify those with highest expression.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from untransformed control plants, control plants transformed with the empty vector, and the pKM24-ibm8 and pKM24-ibm10 transformants was isolated using a DNeasy Plant Mini Kit (Qiagen, Valencia, CA) as described earlier [23]. …”
Section: Methodsmentioning
confidence: 99%
“…b Gene coding for cell wall-degrading enzymes were cloned, and suitable constructs are made with a signal peptide for secretion and c introduced into the plant under control of a constitutive promoter and depending on the substrate type, the secreted enzyme alters the plant cell wall structure (lignin in brown, hemicellulose in red, pectin in green, cellulose in blue) and e boosts bioethanol yields [120,121]. Large numbers of xylanases have been found in a variety of bacteria and fungi, some of which have been cloned, characterized [121][122][123], and expressed in plants [86,87]. The reduction of xylan content in plants to increase cell wall degradability by heterologous expression of xylanases was shown by several research groups [84,86].…”
Section: Hemicellulose Modificationmentioning
confidence: 99%
“…Engineered plants showed a decrease in molecular weight of xylans compared to WT lines; however, sugar release of these plants has not been reported [86]. Similarly, Chatterjee et al [87] successfully expressed a thermophilic xylanase in tobacco without any deleterious effect. In this study, the enzyme activity and transcript analysis have been identified, but there was no information regarding the cell wall composition.…”
Section: Hemicellulose Modificationmentioning
confidence: 99%